On Generation of Micro-Feature on Silicon with an Industrial Laser - M., Ishak; Thet, Thet Mon; Noriah, Bidin; Yap, Tze Chuen (Trans Tech Publications, 2014)
Generation of a micro feature on mono-crystalline silicon surface using an industrial laser is presented. The main objective is to investigate the capability of the industrial laser, Nd:YAG, in generating a micro-feature on silicon surface. The unpolished silicon surface was irradiated with the Nd:YAG laser beam of controlled pulse width and power. In phase 1, the irradiations were done without incorporating an assist gas into the process. In phase 2, the compressed air maintaining its pressure at 4 bars, was supplied as an assist gas during laser irradiation. Design of experiment was adopted to systematically determine the number of experimental runs in each phase as well as to fine tune the important parameters through the statistical analysis. Laser-generated structures were observed under scanning electron microscope. Micrographs reveal that most of the features appear to be cone-like with an almost true circle at the base. The diameter of the cone is found to be as small as 200 µm. The quality of such micro-features and analysis of the effect of the process parameters on the feature quality show that in general, laser pulse width has more appreciable effect than the laser power on the micro-feature geometry as well as quality. Laser irradiation without the assist gas produces better results in terms of a feature size.